Microclimate and thermal comfort of public enclosed courtyards in hot dry regions, with special reference to Tripoli, Libya - Sufeljen, Abdusalam (2014)
With increasing concerns about the implications of climate change and urbanisation, there has been an increased public interest in the quality of urban open spaces in many countries because of its importance for daily people’s lives and urban environment. Recent studies in this field have shown that the microclimatic conditions are very important for people’s comfort in urban open spaces and, therefore, for the use of these spaces. Studying microclimate and thermal conditions in urban open spaces has been increased in the past years. The relationship between the microclimate, thermal comfort and the built urban form is still not understood very well. Further research in this aspect is needed. The courtyard is one of the open space types widely used in the countries of North Africa, Middle East and South Europe. The courtyard is often referred to in literature as a microclimate modifier. Because of this, many studies have been conducted in order to investigate its thermal environment. The majority of these studies dealt with the courtyard as a private space as a part of a building that can contribute to improve the indoor thermal conditions of the surrounding covered areas (its main function is to provide daylight and ventilation into the covered spaces). This study focuses on a particular type of courtyard. It deals with public enclosed courtyards which combine the features of the courtyards and public squares. This type of courtyard is not limited to provide only natural ventilation and natural daylight for the surrounding buildings, but it is mainly designed to offer a public place to perform a variety of activities for people such as social interactions, culture events, recreation, playing, business and many other activities. To the best of my knowledge, there have been no studies done on the microclimate and thermal comfort of courtyards with similar designs (function), particularly in hot dry regions. This study is conducted in Libya where the courtyard is the most common architectural pattern in its cities through all periods of the history. It is conducted in Libya where there is no published research on outdoor thermal comfort. This study investigated the microclimate, thermal comfort and the relationship with the built urban form of public enclosed courtyards in Tripoli city. The general purpose of this study was to develop a database of the thermal environment and subjective responses of people in existing public open spaces in a hot dry climate. The methodology used for this purpose was field studies. Two short-term field surveys were conducted in the two extreme seasons in Libya, one in the cool season day-time and the other one in the hot season day-time. A further field survey was performed during the hot season night-time, where no such study has been conducted in courtyards at this time in the past. In these field studies, extensive environmental measurements have been carried out in parallel to questionnaire surveys with the users of the selected case study sites. Six varied public enclosed courtyards representing three different architecture and urban-built forms of Tripoli city (old city, colonial city, and post-colonial city), were selected for the purpose of this study. The results showed that during both seasons, the microclimatic conditions in the studied courtyards were varied depending mainly on the amount of solar radiation received by their surfaces. Spatial characteristics (architectural form, geometry and surface materials and colours) had important roles in shaping the microclimates of the studied sites during both seasons. The results also showed that the distribution of thermal sensation votes, overall comfort votes and thermal preference votes were different for both seasons, as well as for the sites. Air temperature and then wind speed were found to be the most important determinants of people comfort. The findings of the study also revealed that summer night-time is considered to be of concern for urban thermal comfort in outdoor environments in Tripoli. In general, the findings confirmed a strong relationship between the built urban form (spatial characteristics of the sites), the microclimatic conditions and people’s comfort.